Subjective health status and health-promoting behaviour of nursing students: Subjective health status and health-promoting behaviour - Kang, Se-Won (Advances in Social Sciences Research Journal, 2019)
This descriptive study aimed to investigate the relation between subjective health status and health-promoting behaviour among nursing students. Participants were 177 students from the nursing department of two universities in South Korea. Data were collected from February to March 2018. Data were analysed using mean, standard deviation, analysis of variance, and Scheffe’s test for post hoc using IBM SPSS Statistics 22.0. The distribution of the subjective health status was as follows: poor (39.0%), moderate (35.0%), and good (26.0%). The mean score of health-promoting behaviours was 3.03 (out of 5). In analysing the health-promoting behaviour scores according to subjective health status group, statistically significant differences were seen in exercise and sexual health. As for differences between the groups, the ‘poor’ and ‘good’ groups showed higher scores in ‘exercise’ compared with the ‘moderate’ group. Therefore, subjective health status can affect health-promoting behaviours.